The Stochastic Seismic Response Analysis and Reliability Research on Nonlinear Pile-Soil-Structure Interaction System with Uncertain Parameters - Zhiguang Li, Aihong Zhou, Ying Yuan, Yuanjie Zhao (Forest Chemicals Review)
A new approach is presented to analyze the seismic response of nonlinear pile-soil-structure interaction (PSSI) systems with uncertain parameters subject to the stochastic earthquake. First, the pseudo-excitation approach transforms the stochastic seismic analysis to an accurate analysis of the deterministic harmonic vibration. Second, a small parameter perturbation method is adopted to deal with the uncertain material parameters, while a direct interpolation equivalent linearization model is deduced for simulating the material nonlinearity. Then, the impacts of the variation of shear modulus, damping ratio, density, and Poisson’s ratio on the PSSI system’s stochastic seismic response are verified. Finally, according to the characteristics of the earthquake damage for the PSSI system, an anti-seismic approach is employed to take similar reliability for both pile foundation and structure. In addition, the stochastic seismic response analysis is employed to perform the stochastic dynamic reliability of the PSSI system with uncertain parameters based on the dual design guideline of strength and deformation. According to the results, the response’s variation coefficients and the inputted material parameters have the same magnitude, while the effects of the variation of material parameters on the response magnitude should be considered. The control indexes, i.e., settlement, shear force, and a bending moment of the pile foundation, inter-storey displacement, and inter-storey shear force of structure, decrease while increasing the failure probability.